Technical Change, Technical Efficiency, and Their Impact on Input Demand in the Agricultural and Manufacturing Sectors of Pakistan (The Pakistan Development Review, 1996)
Technical change has been considered as one of the most important determinants of economic growth. In developed economies, a proportionately higher percentage of GDP growth is attributable to technological progress and technical efficiency. However, technical change in developing countries is in its early stages and increased use of factor inputs is still the dominant source of economic growth. An attempt has been made in this paper to analyse technological progress and technical efficiency and their contribution to economic growth along with other factors of production by using more efficient methods in the manufacturing and agriculture sectors of Pakistan. There are a few studies on technological growth and technical efficiency change in Pakistan but they suffer from certain limitations. Most of them use the terms of technical change and productivity synonymously. Further, all of them use Hicks’s formula of neutral technical change and assume that technical change is happening at a constant rate. We have attempted to measure technical change, technical efficiency, and productivity in the form of the Hicks neutral technical change as well as in the form of variable and continuous and discrete technical change. Besides, this paper also analyses the impact of technical change on input demand (i.e., its impact on labour and capital demand) and examines the issue of technical change being either labour-saving or capital-saving. We found that technical change was taking place at a continuous and variable rate. The major contributor to the growth of output and value-added in both sectors was capital, contributing over 50 percent. Labour share was about 20 percent in the agriculture sector and about 10 percent in the manufacturing sector. Technical change share was very significant in manufacturing but not so in agriculture. The manufacturing sector in Pakistan has grown at an annual rate of about 6 percent during 1970s and at 8.7 percent during 1980s, and its share in GDP has increased from 16.5 percent to about 19 percent, but it has failed to generate new employment opportunities for the labour force. The employment growth rate is only about 2 percent.